Virus Amplification - Weirick, Brinley; Klein, Peter; Smith, C. Michael (My University, 2018)
Sorghum is the fifth most produced cereal in the world and a source of nutrients for humans, feeding more than 500 million people in Africa and Asia [1]. It is grown commercially for food, animal feed, fiber and fuel in roughly 100 countries including U.S. [2]. Worldwide, feeding by 150 insect species causes substantial economic damage to sorghum [3]. Besides feeding damage, aphids such as the Corn Leaf Aphid vector Sugarcane mosaic virus (SCMV), Sorghum mosaic virus (SRMV), Maize mosaic virus (MDMV) and Johnson grass mosaic virus (JGMV) [4]. These are Potyviruses, the largest group of the Potyviridae family with 176 members [5] and cause substantial yield losses to sorghum, sugarcane, and maize. SCMV, SRMV, and MDMV are closely related whereas JGMV is more distantly related to them [6]. All have an average 9.7 kb positive-sense single-stranded RNA genome encoding 10 mature proteins in a single large ORF [7].
Keywords: Fall 2018